Synthesis and Biological Activity of Some New β-(2-Benzothiazolyl)-Acryloylamino Acid Derivatives - Ibrahim, T.M.; Gommaa, A.M.; El-Gazzar , M.A.; Radi, A.H.M.; ABD EL-SALAM, A.M. (Asian Journal of Chemistry, 2010)
The synthesis of β-(2-benzothiazolyl) acryloylamino acid methyl esters (II-VII), hydrazides (VIII-XIII) and dipeptide methyl esters (XIV-XIX) are described. The derivatives containing the residues of Ser, Phe, Tyr and Try were found to be active against several microorganisms.